2000
DOI: 10.1097/00001756-200006260-00034
|View full text |Cite
|
Sign up to set email alerts
|

Centrally administered orexin/hypocretin activates HPA axis in rats

Abstract: The effects of i.c.v. administration of orexin/hypocretin on plasma ACTH, corticosterone and c-fos mRNA in the paraventricular nucleus (PVN) of the rat were examined. Plasma ACTH levels were markedly increased at 30 min after i.c.v. administration of orexin-A. Plasma corticosterone levels were significantly increased in a dose-related manner 30 min after i.c.v. administration of orexin-A and orexin-B. In situ hybridization histochemistry revealed that the induction of the c-fos mRNA in the parvocellular divisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(173 citation statements)
references
References 1 publication
8
164
0
1
Order By: Relevance
“…Footshock-sensitive neurons in lateral hypothalamus have been described that project to the PVN (Li and Sawchenko, 1998). Furthermore, hypocretin-1 induces c-Fos expression in the PVN (Ida et al, 2000a) and dose dependently stimulates ACTH and corticosterone release (Hagan et al, 1999;Ida et al, 2000a;Jaszberenyi et al, 2000;Kuru et al, 2000;Samson et al, 2002). Pretreatment with ␣-helical CRF, a CRF antagonist, blocks the corticosterone elevation induced by hcrt (Ida et al, 2000b;Jaszberenyi et al, 2000;Samson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Footshock-sensitive neurons in lateral hypothalamus have been described that project to the PVN (Li and Sawchenko, 1998). Furthermore, hypocretin-1 induces c-Fos expression in the PVN (Ida et al, 2000a) and dose dependently stimulates ACTH and corticosterone release (Hagan et al, 1999;Ida et al, 2000a;Jaszberenyi et al, 2000;Kuru et al, 2000;Samson et al, 2002). Pretreatment with ␣-helical CRF, a CRF antagonist, blocks the corticosterone elevation induced by hcrt (Ida et al, 2000b;Jaszberenyi et al, 2000;Samson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These include feeding behavior (1, 3, 4), behavioral activity (5), sleep/awake (6,7,8), energy balance (9) and neuroendocrinological response (10). In addition to these functions, we have shown that intracisternal but not intraperitoneal injection of orexin-A dosedespondently stimulated gastric acid secretion in conscious rats (11).…”
Section: Introductionmentioning
confidence: 94%
“…For example, the feedingpromoting actions of HCRT may reflect a potentially broader role of HCRT in appetitive processes (Willie et al, 2001). Additionally, ICV HCRT-1 elicits a variety of stresslike physiological and behavioral responses, including activation of the hypothalamo-pituitary-adrenal axis (Jaszberenyi et al, 2000;Kuru et al, 2000), increased c-fos expression (España et al, 2003), locomotor activation, grooming, and the chewing of inedible material (Nakamura et al, 2000;España et al, 2001). Intra-VTA infusions of HCRT-1 also provoked certain stress-like behaviors, including grooming.…”
Section: Hcrt-da Interactions In Aversive and Appetitive Conditionsmentioning
confidence: 99%